Regiocontrolled Halogen Dance and In Situ Transmetalation of Pyrroles Directed by the α-Substituent - Matsuyama, Daichi; Okumi, Tatsuki; Mori, Atsunori; Okano, Kentaro (Synlett, 2024)
Multiply substituted pyrroles are found in medicines, natural products, and functional materials. A general method for introducing functionality on the pyrrole ring is thus required. Herein, a regiocontrolled halogen dance reaction and an in situ transmetalation of α-functionalized bromopyrroles are reported. Selective generation of the isomeric pyrrolylmetal species was achieved by using an ethyl ester or a phenyl group at the α-position of the pyrrole and by switching between the halogen dance reaction and in situ transmetalation. These reactions proceeded smoothly when an N,N-dimethylsulfamoyl group was attached to the pyrrole nitrogen atom, providing the corresponding products in 68% to quantitative yields on 1-mmol scale. This method was applicable to the formal synthesis of Kendine 91.
Keywords: deprotonation; halogen dance; in situ transmetalation; organometallic reagents; pyrroles; regioselectivity